Marketing Mix of Dry Bulk Market Share at Jamrud Terminal - Dian Arisanti; Mudayat Mudayat; Isabela Kilimandu (IJEBD (International Journal of Entrepreneurship and Business Development), 2022)
Purpose: The purpose of this study is to find out and analyze how the marketing mix affects the market share of loading and unloading dry bulk at Jamrud Terminal.